VACÍOS LEGALES Y CONSTITUCIONALES EN LA APLICACIÓN DE LA JUSTICIA INDIGENA” - Carrión Merino, Alex René (2020)
The present research work is entitled "Legal and constitutional gaps in the application of indigenous justice", since the application of this type of customary law in our country is generating violation of constitutional rights and principles, I will depart from two constitutional premises for later Go developing the theme and find the problem that is afflicting our society. Article 167 of the constitution tells us that the power to administer justice is exercised by the judicial function and by the other organs and functions established in the Constitution. On the other hand, Article 171 of the Constitution talks about indigenous communities, peoples and nationalities and tells us that the authorities of these places will exercise jurisdictional functions, based on their ancestral traditions and their own right, within their territory. The Indigenous Justice is the set of norms that based on values and cultural principles of these peoples, with their own procedures and practices that regulate social life in the community and the territory. The reparations to the transgressions to these norms can be by means of the recomposition, the compensation, and / or the remediation of the damages caused, and not only by way of the punishment, that is the preponderant form in the Ordinary Justice. In article 76 of our constitution the right to due process is guaranteed and it tells us of all the guarantees that this due process will have, for example, that corresponds to all administrative or judicial authorities, to guarantee compliance with the norms and rights of the parties, paragraph 7 of this article tells us that no one may be deprived of the right to defense at any stage or degree of the 6 procedure, also the guarantee of having the time and adequate means to prepare his defense, in procedures judicial, be assisted by a lawyer or lawyer of your choice or by public defender or defender; You can not restrict access or free and private communication with your defender, no one can be tried more than once for the same cause and matter. The cases resolved by the indigenous jurisdiction must be considered for this purpose. Starting from these articles we can say that the constitution shows the rights and guarantees of the people to have a due process, it can also be deduced the inclusion that the state does for the indigenous peoples and communities, giving them the power to solve their own problems in base to their ancestral customs, whenever these go against the constitution and its principles. The application of indigenous justice can affect other constitutional principles, due to which the ideal would be the search of a harmony between the processes, delimiting when the indigenous justice will have competition or not to act.